Activation of liver X receptors inhibits experimental fibrosis by interfering with interleukin-6 release from macrophages - Beyer, Christian; Huang, Jingang; Beer, Juergen; Zhang, Yun; Palumbo-Zerr, Katrin; Zerr, Pawel; Distler, Alfiya; Dees, Clara; Maier, Christiane; Munoz, Louis; Krönke, Gerhard; Uderhardt, Stefan; et al. (Annals of the Rheumatic Diseases, 2015)
To investigate the role of liver X receptors (LXRs) in experimental skin fibrosis and evaluate their potential as novel antifibrotic targets.We studied the role of LXRs in bleomycin-induced skin fibrosis, in the model of sclerodermatous graft-versus-host disease (sclGvHD) and in tight skin-1 (Tsk-1) mice, reflecting different subtypes of fibrotic disease. We examined both LXR isoforms using LXR?-, LXR?- and LXR-?/?-double-knockout mice. Finally, we investigated the effects of LXRs on fibroblasts and macrophages to establish the antifibrotic mode of action of LXRs.LXR activation by the agonist T0901317 had antifibrotic effects in bleomycin-induced skin fibrosis, in the sclGvHD model and in Tsk-1 mice. The antifibrotic activity of LXRs was particularly prominent in the inflammation-driven bleomycin and sclGvHD models. LXR?-, LXR?- and LXR?/?-double-knockout mice showed a similar response to bleomycin as wildtype animals. Low levels of the LXR target gene ABCA-1 in the skin of bleomycin-challenged and control mice suggested a low baseline activation of the antifibrotic LXR signalling, which, however, could be specifically activated by T0901317. Fibroblasts were not the direct target cells of LXRs agonists, but LXR activation inhibited fibrosis by interfering with infiltration of macrophages and their release of the pro-fibrotic interleukin-6.We identified LXRs as novel targets for antifibrotic therapies, a yet unknown aspect of these nuclear receptors. Our data suggest that LXR activation might be particularly effective in patients with inflammatory disease subtypes. Activation of LXRs interfered with the release of interleukin-6 from macrophages and, thus, inhibited fibroblast activation and collagen release.
EVALuna2:12871

Inhibition of phosphodiesterase 4 (PDE4) reduces dermal fibrosis by interfering with the release of interleukin-6 from M2 macrophages - Maier, Christiane; Bergmann, Christina; Weinkam, Rita; Kittan, Nicolai; Schett, Georg; Distler, Jörg; Beyer, Christian; Ramming, Andreas (Annals of the Rheumatic Diseases, 2017)
To investigate the disease-modifying effects of phosphodiesterase 4 (PDE4) inhibition in preclinical models of systemic sclerosis (SSc).We studied the effects of PDE4 inhibition in a prevention and a treatment model of bleomycin-induced skin fibrosis, in the topoisomerase mouse model as well as in a model of sclerodermatous chronic graft-versus-host disease. To better understand the mode of action of PDE4 blockade in preclinical models of SSc, we investigated fibrosis-relevant mediators in fibroblasts and macrophages from healthy individuals and patients suffering from diffuse-cutaneous SSc on blockade of PDE4.Specific inhibition of PDE4 by rolipram and apremilast had potent antifibrotic effects in bleomycin-induced skin fibrosis models, in the topoisomerase I mouse model and in murine sclerodermatous chronic graft-versus-host disease. Fibroblasts were not the direct targets of the antifibrotic effects of PDE4 blockade. Reduced leucocyte infiltration in lesional skin on PDE4 blockade suggested an immune-mediated mechanism. Further analysis revealed that PDE4 inhibition decreased the differentiation of M2 macrophages and the release of several profibrotic cytokines, resulting in reduced fibroblast activation and collagen release. Within these profibrotic mediators, interleukin-6 appeared to play a central role.PDE4 inhibition reduces inflammatory cell activity and the release of profibrotic cytokines from M2 macrophages, leading to decreased fibroblast activation and collagen release. Importantly, apremilast is already approved for the treatment of psoriasis and psoriatic arthritis. Therefore, PDE4 inhibitors might be further developed as potential antifibrotic therapies for patients with SSc. Our findings suggest that particularly patients with inflammation-driven fibrosis might benefit from PDE4 blockade.
EVALuna2:13394

Nintedanib macrophage activation and ameliorates vascular and fibrotic manifestations in the Fra2 mouse model of systemic sclerosis - Huang, Jingang; Maier, Christiane; Zhang, Yun; Soare, Alina; Dees, Clara; Beyer, Christian; Harre, Ulrike; Chen, Chih-Wei; Distler, Oliver; Schett, Georg; Wollin, Lutz; Distler, Jörg (Annals of the Rheumatic Diseases, 2017)
Nintedanib is an inhibitor targeting platelet-derived growth factor receptor, fibroblast growth factor receptor and vascular endothelial growth factor receptor tyrosine kinases that has recently been approved for the treatment of idiopathic pulmonary fibrosis. The aim of this study was to analyse the effects of nintedanib in the fos-related antigen-2 (Fra2) mouse model of systemic sclerosis (SSc).The effects of nintedanib on pulmonary arterial hypertension with proliferation of pulmonary vascular smooth muscle cells (PVSMCs) and luminal occlusion, on microvascular disease with apoptosis of microvascular endothelial cells (MVECs) and on fibroblast activation with myofibroblast differentiation and accumulation of extracellular matrix were analysed. We also studied the effects of nintedanib on the levels of key mediators involved in the pathogenesis of SSc and on macrophage polarisation.Nintedanib inhibited proliferation of PVSMCs and prevented thickening of the vessel walls and luminal occlusion of pulmonary arteries. Treatment with nintedanib also inhibited apoptosis of MVECs and blunted the capillary rarefaction in Fra2-transgenic mice. These effects were associated with a normalisation of the serum levels of vascular endothelial growth factor in Fra2 mice on treatment with nintedanib. Nintedanib also effectively blocked myofibroblast differentiation and reduced pulmonary, dermal and myocardial fibrosis in Fra2-transgenic mice. The antifibrotic effects of nintedanib were associated with impaired M2 polarisation of monocytes and reduced numbers of M2 macrophages.Nintedanib targets core features of SSc in Fra2-transgenic mice and ameliorates histological features of pulmonary arterial hypertension, destructive microangiopathy and pulmonary and dermal fibrosis. These data might have direct implications for the ongoing phase III clinical trial with nintedanib in SSc-associated interstitial lung diseas
EVALuna2:13441

Pharmacological inhibition of porcupine induces regression of experimental skin fibrosis by targeting Wnt signalling - Chen, Chih-Wei; Beyer, Christian; Liu, Jun; Maier, Christiane; Li, Chun; Thuong Trinh-Minh; Xu, Xiaohan; Cole, Stuart H.; Hsieh, Mindy H.; Ng, Nicholas; Althage, Alana; Meeusen, Shelly; et al. (Annals of the Rheumatic Diseases, 2017)
Wnt signalling has been implicated in activating a fibrogenic programme in fibroblasts in systemic sclerosis (SSc). Porcupine is an O-acyltransferase required for secretion of Wnt proteins in mammals. Here, we aimed to evaluate the antifibrotic effects of pharmacological inhibition of porcupine in preclinical models of SSc.The porcupine inhibitor GNF6231 was evaluated in the mouse models of bleomycin-induced skin fibrosis, in tight-skin-1 mice, in murine sclerodermatous chronic-graft-versus-host disease (cGvHD) and in fibrosis induced by a constitutively active transforming growth factor-?-receptor I.Treatment with pharmacologically relevant and well-tolerated doses of GNF6231 inhibited the activation of Wnt signalling in fibrotic murine skin. GNF6231 ameliorated skin fibrosis in all four models. Treatment with GNF6231 also reduced pulmonary fibrosis associated with murine cGvHD. Most importantly, GNF6231 prevented progression of fibrosis and showed evidence of reversal of established fibrosis.These data suggest that targeting the Wnt pathway through inhibition of porcupine provides a potential therapeutic approach to fibrosis in SSc. This is of particular interest, as a close analogue of GNF6231 has already demonstrated robust pathway inhibition in humans and could be available for clinical trials.
EVALuna2:13348

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Stimulation of the soluble guanylate cyclase (sGC) inhibits fibrosis by blocking non-canonical TGF? signalling - Beyer, Christian; Zenzmaier, Christoph; Palumbo-Zerr, Katrin; Mancuso, Rossella; Distler, Alfiya; Dees, Clara; Zerr, Pawel; Huang, Jingang; Maier, Christiane; Pachowsky, Milena; Friebe, Andreas; Sandner, Peter; et al. (Annals of the Rheumatic Diseases, 2015)
We have previously described the antifibrotic role of the soluble guanylate cyclase (sGC). The mode of action, however, remained elusive. In the present study, we describe a novel link between sGC signalling and transforming growth factor ? (TGF?) signalling that mediates the antifibrotic effects of the sGC.Human fibroblasts and murine sGC knockout fibroblasts were treated with the sGC stimulator BAY 41-2272 or the stable cyclic guanosine monophosphate (cGMP) analogue 8-Bromo-cGMP and stimulated with TGF?. sGC knockout fibroblasts were isolated from sGCI(fl/fl) mice, and recombination was induced by Cre-adenovirus. In vivo, we studied the antifibrotic effects of BAY 41-2272 in mice overexpressing a constitutively active TGF-?1 receptor.sGC stimulation inhibited TGF?-dependent fibroblast activation and collagen release. sGC knockout fibroblasts confirmed that the sGC is essential for the antifibrotic effects of BAY 41-2272. Furthermore, 8-Bromo-cGMP reduced TGF?-dependent collagen release. While nuclear p-SMAD2 and 3 levels, SMAD reporter activity and transcription of classical TGF? target genes remained unchanged, sGC stimulation blocked the phosphorylation of ERK. In vivo, sGC stimulation inhibited TGF?-driven dermal fibrosis but did not change p-SMAD2 and 3 levels and TGF? target gene expression, confirming that non-canonical TGF? pathways mediate the antifibrotic sGC activity.We elucidated the antifibrotic mode of action of the sGC that increases cGMP levels, blocks non-canonical TGF? signalling and inhibits experimental fibrosis. Since sGC stimulators have shown excellent efficacy and tolerability in phase 3 clinical trials for pulmonary arterial hypertension, they may be further developed for the simultaneous treatment of fibrosis and vascular disease in systemic sclerosis.
EVALuna2:12978